(untitled) (Global Journal of Science Frontier Research, 2022)
This research provides a brief review on several topics as a foundation to comprehend the current situation on water and hydrological resources management and monitoring at a local scale, considering the case of the Tabacay river micro-basin the southeast of Ecuador. This study is performed in aims to explore the data collected by representative meteorological and pluviometry stations of the corresponding geographical space withing the micro-basin. In this context, a comparative analysis on rainfall for the recent years is provided. It also presents the evaluation of the existing challenges in the water and sanitation management and further recommendations for control and use of the natural resources in subject.